The Association Between Body Dissatisfaction and Depression: An Examination of the Moderating Effects of Gender, Age, and Weight Status in a Sample of Chinese Adolescents. Issue 2 (27th April 2015) - Chen, Gui; Guo, Guiping; Gong, Jingbo; Xiao, Shuiyuan
Abstract : The current study investigated the moderating effects of gender, age, and weight status on the relationship between body dissatisfaction and depression among adolescents. Data were collected on body dissatisfaction, depression, and demographic characteristics from a convenience sample of 1, 101 adolescents (505 girls, 596 boys). The relationship between body dissatisfaction and depression differed significantly by weight status (β = −0.318, p < .01), but not gender or age. In addition, their association varied across weight status only in males (βs = 0.501, 0.240, and 0.178 for underweight, normal weight, and overweight respectively, p s < .05) and the early adolescence group (βs = 0.523, 0.282, 0.297 for underweight, normal weight, and overweight respectively, p s < .01). The findings indicated that the association of body dissatisfaction with depression was significant among nearly all weight-status groups of adolescents, and varied across weight status among males and early adolescence groups. This suggests that the prevention programs that aim to reduce depression by reducing body dissatisfaction in adolescents should include all weight-status groups, and pay close attention to underweight adolescents (especially underweight boys and early adolescents who are underweight).